2021
DOI: 10.1002/anie.202114862
|View full text |Cite
|
Sign up to set email alerts
|

Relating Conformational Equilibria to Conformer‐Specific Lipophilicities: New Opportunities in Drug Discovery

Abstract: Efficient drug discovery is based on a concerted effort in optimizing bioactivity and compound properties such as lipophilicity, and is guided by efficiency metrics that reflect both aspects. While conformation-activity relationships and ligand conformational control are known strategies to improve bioactivity, the use of conformer-specific lipophilicities (logp) is much less explored. Here we show how conformer-specific logp values can be obtained from knowledge of the macroscopic logP value, and of the equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 43 publications
(19 reference statements)
2
31
0
Order By: Relevance
“…A recent elegant study Chemistry-A European Journal dealing with mono-and difluorinated pyrrolidine / piperidine derivatives showed that conformational equilibria can lead to experimentally measurable effects on the LogP values. [53] Interestingly, a different order of lipophilicity was observed for acyclic derivatives 3.0β-δ and 4.0β-δ: δ < γ < β. In other words, while acyclic δ and γ isomers demonstrated behavior like that of cycloalkanes, acyclic β isomers had considerably…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent elegant study Chemistry-A European Journal dealing with mono-and difluorinated pyrrolidine / piperidine derivatives showed that conformational equilibria can lead to experimentally measurable effects on the LogP values. [53] Interestingly, a different order of lipophilicity was observed for acyclic derivatives 3.0β-δ and 4.0β-δ: δ < γ < β. In other words, while acyclic δ and γ isomers demonstrated behavior like that of cycloalkanes, acyclic β isomers had considerably…”
Section: Resultsmentioning
confidence: 94%
“…For a more detailed discussion of these observations, a thorough conformational analysis of amides 3 and 4 in aqueous and organic media is required, which is to be performed in the upcoming work. A recent elegant study dealing with mono‐ and difluorinated pyrrolidine / piperidine derivatives showed that conformational equilibria can lead to experimentally measurable effects on the Log P values [53] …”
Section: Resultsmentioning
confidence: 99%
“…Conformation-specific lipophilicities of fluorinecontaining piperidines and pyrrolidines were recently discussed in the literature. [19]…”
Section: Lipophilicitymentioning
confidence: 99%
“…A number of insightful studies that summarize the impact of various fluorination patterns on the compound's physicochemical and pharmacokinetic parameters started to emerge over the last decade. [15][16][17][18][19] In one of their contributions, Müller and co-authors suggested that the dipole moment of the vicdifluoro moiety is 1.4 times higher than that of the gem-difluoro moiety based on a simple vector analysis approach. [20] Later on, this assumption was experimentally confirmed by showing a lipophilicity decrease in vic-difluoro-substituted derivatives A1 and A2, and a basicity decrease in A1 compared to their gemdifluoro-substituted counterparts (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen containing aromatic compounds are widespread in small-molecule drugs, pharmaceuticals, agrochemicals and natural products. [1][2][3][4][5][6] Among nitrogen containing compounds, azaarylmethyl amines frequently exhibit bioactivity, including antitumor, 7 antihistamine 8 and anti-HIV properties. 9 The preparation of enantioenriched α-azaarylmethyl amines has been inspired, in part, by a drive from the pharmaceutical industry to increase the number of amino groups in molecules to be tested for bioactivity.…”
Section: Introductionmentioning
confidence: 99%